Small is beautiful? How the introduction of mini futures contracts affects the regular contract - Stefan Greppmair; Erik Theissen (University of Cologne, Centre for Financial Research (CFR), 2019)
We analyze how the introduction of a mini futures contract affects the liquidity of the regular contract. We use a panel data set that covers more than 20 years and more than 20 contracts. We use a traditional difference-in-differences methodology as well as a synthetic control group approach (Abadie and Gardeazabal (2003), Abadie, Diamond and Hainmueller (2015)). We find that the liquidity of the regular contracts increases and the volatility decreases upon the introduction of a mini futures contract when the regular contract is traded electronically whereas the reverse is true when it is floor-traded. While total trading volume increases upon the introduction of the mini contract, the volume of the regular contracts does not change significantly. Overall, our results imply that the introduction of mini futures contracts is beneficial. They also confirm the superiority of electronic trading over floor-based trading.
Keywords: G10; G15; 330; Stock index futures; Mini futures; Liquidity; Market quality